Advances in interlayer bonding in fused deposition modelling: a comprehensive review - Mohamed A. E. Omer; Ibrahim Abdelfadeel Shaban; Abdel-Hamid Mourad; Hussien Hegab (Virtual and Physical Prototyping)
Fused deposition modeling (FDM) has established itself as a major additive manufacturing technology for the production of parts made of polymer and composite materials. A critical challenge in FDM is achieving strong interlayer bonding (IB), which worsens mechanical anisotropy and compromises the overall functionality of fabricated parts. To overcome this limitation, researchers have developed a range of advanced techniques, including pre-printing modifications (e.g. filament material modification), in-process interventions (e.g. preheating, vibration, and ultrasonic-assisted FDM), and post-processing methods (e.g. ultrasonic strengthening, annealing, microwave welding, and electromagnetic induction welding). Each of these techniques has been investigated, showing its pros and cons. This article also explores recent advancements aimed at enhancing IB, explaining their underlying mechanisms, highlighting key results, and critically evaluating their overall effectiveness. This review synthesises the state-of-the-art in IB enhancement strategies and their influence on resultant part properties. Consequently, further investigation into optimising existing methods and developing innovative approaches is essential for realising the full potential of FDM in advanced manufacturing applications.